Implementasi Sistem Informasi Manajemen Inventaris Berbasis Web Di Pusat Teknologi Informasi Dan Komunikasi – BPPT - Alief Maulana; Muhammad Sadikin; Arief Izzuddin (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2018)
Web-based invertasis information system can be a solution for management of investment information data that has done manually in the environment of Information and Communication Technology Center - BPPT. In addition, the DIPA (Annual Budget Implementation) program held annually at PTIK-BPPT requires the monitoring or reporting of existing asset data. Using a web-based inventory information system can help ease and speed up the procurement process of DIPA programs, as well as manage stock options, asset lending and asset recovery assets and demand for consumables that have been manually turned into web-based applications. Use of web-based information system applications can be a solution to manage inventory. The use of Snape-IT applications can be an option, since the content available in the Snape-IT application supports the existing needs of the company, but much of the content must be tailored to the business of inventory management processes that are still manual